Art in the Hinge : the collection of the European Patent Office in The Hague - Poalas, Monica; Gemeentemuseum, Den Haag (Den Haag : European Patent Office München Gemeentemuseum Den Haag, 2004)
Heringa & Van Kalsbeek ; Smulders, Margriet ; Trenkwalder, Elmar ; Falconi, Lucia ; de Jong, Petra ; Oberer, Klaus ; Flynn, David John ; Mohr, Tanja ; van Vught, Reinoud ; Zeniuk, Jerry ; Geier, Helmut ; Boissel, Bernard ; Paladini, Marco ; Poth, Uwe ; Bonger, Paul ; Nardin, Patric ; van Vreden, Martin ; Groom, Jon ; Carter, John ; Paal, Dany ; Tischler Wood, Alma ; Yalcindag, Ekrem ; Dekkers, Ger ; Trespi, Alex ; Masuyama, Hiroyuki ; Rehm, Dieter ; Korfmann, Katrin ; Rihs, Christoph ; Geelen, Guido ; Chafes, Rui ; Jung, Dieter ; Miura, Yoshiyuki ; Hennissen, Nol ; Hein, Jeppe ; Spaans, Jean-Marc ; Fischer, Roland ; Winner, Gerd ; Zaumseil, Uta ; Davar, Katja ; Twelker, Jochen
Publication on the occasion of the presentation of the art collection 'Art in the Hinge: the collection of the European Patent Office in The Hague' at the Gemeentemuseum in Den Haag, 27.04.2004
boek